2015
DOI: 10.1210/jc.2014-3677
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Coding Genetic Variants Influencing Diabetes-Related Serum Biomarkers and Their Impact on Risk of Type 2 Diabetes

Abstract: The identified loci influence processes related to insulin signaling, cell communication, immune function, apoptosis, DNA repair, and oxidative stress, all of which could provide a rationale for novel diabetes therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 36 publications
(29 reference statements)
1
23
0
Order By: Relevance
“…9p21 in CDKN2A, CDKN2B, and 1p13 near CELSR2-PSRC1-SORT1 also showed association with other disease. Ahluwalia et al [31] tested the 11 biomarker-associated SNPs for association with T2D in Danish samples and found significant statistical associations for CELSR2 SNPs [OR=1.11 (1.05-1.18), P=1.2×10 -3 ], respectively. rs646776 near CELSR2 was associated with an increased fasting serum insulin like growth factor binding protein 1 (IGFBP1) level and a decreased risk of T2D [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9p21 in CDKN2A, CDKN2B, and 1p13 near CELSR2-PSRC1-SORT1 also showed association with other disease. Ahluwalia et al [31] tested the 11 biomarker-associated SNPs for association with T2D in Danish samples and found significant statistical associations for CELSR2 SNPs [OR=1.11 (1.05-1.18), P=1.2×10 -3 ], respectively. rs646776 near CELSR2 was associated with an increased fasting serum insulin like growth factor binding protein 1 (IGFBP1) level and a decreased risk of T2D [31].…”
Section: Discussionmentioning
confidence: 99%
“…Ahluwalia et al [31] tested the 11 biomarker-associated SNPs for association with T2D in Danish samples and found significant statistical associations for CELSR2 SNPs [OR=1.11 (1.05-1.18), P=1.2×10 -3 ], respectively. rs646776 near CELSR2 was associated with an increased fasting serum insulin like growth factor binding protein 1 (IGFBP1) level and a decreased risk of T2D [31]. Gaulton KJ et al [32] observed four loci that each had two distinct association signals, CDKN2A-CDKN2B, diacylglycerol kinase beta (DGKB), melanocortin 4 receptor, (MC4R) and gastric inhibitory polypeptide receptor, (GIPR), with each locus represented by noncoding index variants.…”
Section: Discussionmentioning
confidence: 99%
“…Informed written consent was obtained from all subjects before participation. The genetic association analyses were performed in three Danish study cohorts (Inter99, Health2006 and Health2008) that have been described previously elsewhere:21 (1) Inter99 (ClinicalTrials.gov ID-no: NCT00289237) is a population-based study for ischaemic heart disease;22 (2) Health2006 (Ethical Committee approval number: KA20060011) is a population-based study comprising individuals aged between 18 and 69 years from the South Western part of greater Copenhagen area 23. This study was designed to address chronic health issues; (3) Health2008 (Ethical Committee approval number: KA20060011) is a cross-sectional population-based study 24…”
Section: Methodsmentioning
confidence: 99%
“…DNA extraction, genotyping and genotype call processing has been described previously 21 25. A total of 8445 individuals (n Inter99 : 5420, n Health2006 : 2442, n Health2008 : 583) with complete phenotype and genotype data participated for the serum TSH association analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation